THE UNITED KINGDOM HAS A SPECIAL TEXTBOOK FOR DETECTING FACTS OF CORRUPTION - xidirov, xoshim (FILOLOGIYA UFQLARI JURNALI, 2021)
THE UNITED KINGDOM HAS A SPECIAL TEXTBOOK FOR DETECTING FACTS OF CORRUPTION